Gênero Textual - Notícia de Jornal - Fernandes, Maria Luiza da Silva; Bettiol , Maryella Alexandra Barreto; Carraro, Marcia Regina Simpioni (REVISTA PROGRAMA A UNIÃO FAZ A VIDA_____________________________________________________________________________________________________________, 2021)
>>> ver pdf